13.3k views
5 votes
Help ASAP

Help ASAP
use completing the square to rewrite quadratic function into the form y=a(x+h)²+k
f (x) =4x²+6x-3 (1 point)​

Help ASAP Help ASAP use completing the square to rewrite quadratic function into the-example-1
User Kischa
by
5.7k points

1 Answer

2 votes

Answer:

The second:
\bold{f (x) =4(x+\frac34)^2-\frac{21}4}

Explanation:


f (x) =4x^2+6x-3\\\\f (x) =4(x^2+\frac64x]-3\\\\f (x) =4[x^2+2\cdot x\cdot\frac34+(\frac34)^2-(\frac34)^2]-3\\\\f (x) =4[(x+\frac34)^2-(\frac34)^2]-3\\\\f (x) =4(x+\frac34)^2-4(\frac34)^2-3\\\\f (x) =4(x+\frac34)^2-\frac94-\frac{12}4\\\\\underline{f (x) =4(x+\frac34)^2-\frac{21}4}

User Chris Catignani
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.